KNOWLEDGE, ATTITUDES, ADVERTISING-RELATED FACTORS AND VITAMIN USE BEHAVIORS AMONG PHARMACY STUDENTS IN VIET NAM (Vietnam Journal of Community Medicine, 2026)
Objectives: To assess knowledge, attitudes, exposure to and perceived influence of advertising, and vitamin use behaviors of pharmacy students as well as their associations among these factors.Materials and methods: A cross-sectional study was conducted among 414 pharmacy students using a structured questionnaire.Results: Students demonstrated relatively good knowledge of vitamins (8.75 ± 1.77/10) and a cautious, evidence-oriented attitude (3.84 ± 0.64). Although exposure to vitamin advertising was fairly frequent, the perceived influence of advertising was moderate (2.87 ± 0.84). In the past six months, 82.61% of students that had used or were currently using vitamins, most commonly vitamins C and E. Logistic regression analysis showed that an evidence-oriented attitude was independently associated with a reduced likelihood of purchasing vitamins immediately after advertising exposure (OR = 0.33; 95% CI: 0.16–0.66; p = 0.002).Conclusions: Among pharmacy students, attitudes toward vitamins and advertising were more strongly associated with purchasing behaviour than knowledge level or advertising exposure alone, highlighting the importance of fostering evidence-based attitudes and critical appraisal skills to support rational vitamin use and responsible counseling.
Keywords: vitamins; advertising; attitudes; purchasing behaviour; pharmacy students.